PERANAN KEJAKSAAN REPUBLIK INDONESIA DALAM PEMBERANTASAN KORUPSI DI NEGARA DEMOKRASI (Role of The Attorney General of Indonesia in Eradicating Corruption in State Democracy) - Suharyo Suharyo (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2016)
PERANAN KEJAKSAAN REPUBLIK INDONESIADALAM PEMBERANTASAN KORUPSI DI NEGARA DEMOKRASI(Role of The Attorney General of Indonesia in Eradicating Corruption in State Democracy) The Attorney General of Indonesia plays a strategic position in corruption eradication. Since IndonesiaIndependent Day on 17 August 1945 until now, the attorney general keeps eradicate the corruption. As one of the elements of criminal justice system of the democracy state refers to the Act No.16/2004 on the Attorney General of Republic of Indonesia, and also a concern with the Act No.8/1981 on the Criminal Code (KUHAP). Corruption eradication is ruled and stipulated on the Act No.31/1999 on Corruption Eradication Jo the Act No.20/2001, and supported the Act No.8/2010 on the Criminal Act of Money Laundering . Questions of this research were what obstacles of corruption eradication in attorneys and how to make it effective? It was a normative-juridical method. It was an impression that the Attorney General has no dare to enforce the law for the elite politician, local officials (governors,majors) because of their strong relationship with. This phenomenon triggered scholars to do long march and protest to the Attorney General to be consistent and responsive in corruption eradication. Good governance and bureaucracy reform had no big impact, the meaning of